Impact of a Low Interest Rate Environment - Global Liquidity Spillovers and the Search-for-yield - Ansgar Belke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
On 10 January 2013 the ECB Governing Council decided “to keep the key ECB interest rates unchanged” based on an assessment of a ,contained` inflationary pressure and a weak economic activity, a contraction of real GDP in second and third quarter of 2012. Similar decisions have been taken by other leading central banks around the globe. This paper assesses and comments on several aspects of the implied low interest rate environment. It contains some general considerations with respect to the current low interest rate environment in advanced economies. It then deals with potential conflicts between monetary policy and financial stability in a low interest rate environment. Moreover, more practical implications for the necessity of supervision of pension funds and the insurance sector are derived. The paper also assesses the investment opportunities for retail investors in such an environment. Finally, we single out examples of main beneficiaries and losers from a low interest rate environment.
Keywords: E58; F33; G22; G23; 330; Global liquidity; central banks and their policies; financial repression; low interest rates; insurance companies; pension funds